A brief look at the role of monocyte chemoattractant protein-1 (CCL2) in the pathophysiology of psoriasis. (October 2018) - Behfar, Shadi; Hassanshahi, Gholamhossein; Nazari, Alireza; Khorramdelazad, Hossein
Highlights: Involvement of CCL2 in the pathogenesis of PsO. CCR2/CCL2 is a functional axis in monitoring the progression of PsO. CCR2/CCL2 may offer a new therapeutic approach for the treatment of PsO. Abstract: Psoriasis (PsO) is a chronic skin disorder resulting from the imbalanced interaction between infiltrating immune cells and keratinocytes. These immune cells, including monocytes, are able to mediate the immune responses in inflamed skin lesions. Chemokines are responsible for the recruitment of leukocytes to sites of inflammation. In patients with PsO, the keratinocytes are the main source of monocyte chemotactic protein 1 (MCP-1/CCL2), which is a CC chemokine. After CCL2 binds to the chemokine receptor CCR2, which mainly is expressed on the surface of monocytes, the monocytes differentiate into macrophages and migrate from the blood stream to sites of inflammation. This process can cause the formation of lesions. Accordingly, it has been hypothesized that CCL2 could be a potential biomarker to monitor the progression of PsO. Thus, evidence suggests that there could be a potential role for CCR2 and CCL2 during treatment of PsO and to prevent its further development. For example, to modify the course of PsO, efforts have been made to inhibit or modulate the CCR2/CCL2 axis. However, before exploring the targeting of the CCR2/CCL2 axis in a clinical setting, better understanding of the different molecular aspects of PsO is required.